34. PERAN ORGANIZATION FOR ECONOMIC AND DEVELOPMENT DALAM MENANGGULANGI PRAKTIK TAX CRIME DI INDONESIA STUDI KASUS: TRANSFER PRICING DI INDONESIA TAHUN 2003 – 2012 - Karomatunnisa, Ichda Rizqoh; Susiatiningsih, Hermini; Putranti, Ika Riswanti (Journal of International Relations, 2016)
Taxes are major sources of income for Indonesia, in which taxes contribute 74% - 80% oftotal revenue. The practice of transfer pricing is a problem faced by Indonesia related taxrevenue. Transfer pricing causes a potential loss in state revenue from the tax sector.Between 2003 to 2012, Indonesia had suffered a loss of US $ 152.154 billion. The amountof loss encouraged Indonesia to take various efforts to solve this problem, such ascooperation with the OECD. This study aims to explain the role undertaken by the OECDin tackling transfer pricing practices in Indonesia. The method used in this research isqualitative descriptive type-explanation. Liberal institutionalist theory and the concept ofthe role by Biddle and Biddle are used to analyze the role of the OECD in dealing withtransfer pricing practices in Indonesia. Through this partnership, the role played by OECDgiving seminars, counseling, also training to improve the knowledge and expertise of theIndonesian tax authorities. The OECD also provides an opportunity for Indonesian taxinvestigators are able to participate in OECD’s the Tax Academy. OECD also has BEPSProject to address the Base Erosion and Profit Shifting (BEPS) among multinational thatincludes program management of transfer pricing activities. In this regard, the OECDfocuses on the provision of advice related to legal or tax policy and help increase theability of the tax investigators.